Optimizing Essay Writing Skills through Short Film Media: A Classroom Action Research in Grade XII of SMK Parungponteng - Aglia, Arla; Saputra, Moch; Yohandoko, Setyo (Communication In Research And Publications, 2024)
This research uses the Classroom Action Research (PTK) method with a spiral model to improve the ability to write essay texts through the use of short film media in class XII of Parungponteng Vocational School. Teachers have shown improvement in lesson planning and implementation using short film media. Evaluation of learning outcomes shows a significant increase, with classical completion reaching 100%. Students' abilities in text structure, linguistic rules and writing (mechanics) also increase. Improvement and reflection on the learning process plays an important role in improving the quality of learning and student learning outcomes.